Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.eclinm.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Outcomes After Neonatal Encephalopathy in Uganda: A Cohort Study

Abstract: BackgroundNeonatal encephalopathy (NE) is a leading cause of global child mortality. Survivor outcomes in low-resource settings are poorly described. We present early childhood outcomes after NE in Uganda.MethodsWe conducted a prospective cohort study of term-born infants with NE (n = 210) and a comparison group of term non-encephalopathic (non-NE) infants (n = 409), assessing neurodevelopmental impairment (NDI) and growth at 27–30 months. Relationships between early clinical parameters and later outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…Globally, the last three decades have witnessed considerable decline in under five mortality, but neonatal mortality has not mirrored this feat [1]. Birth asphyxia now accounts for about a quarter of newborn deaths and is associated with significant morbidity among survivors, who suffer disabling motor and cognitive deficits [1][2]. There is currently significant global variation in morbidity and mortality among neonates with asphyxia, as greater than 95% of all asphyxia-related deaths and impairment in these group occur in low resource settings [3].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the last three decades have witnessed considerable decline in under five mortality, but neonatal mortality has not mirrored this feat [1]. Birth asphyxia now accounts for about a quarter of newborn deaths and is associated with significant morbidity among survivors, who suffer disabling motor and cognitive deficits [1][2]. There is currently significant global variation in morbidity and mortality among neonates with asphyxia, as greater than 95% of all asphyxia-related deaths and impairment in these group occur in low resource settings [3].…”
Section: Introductionmentioning
confidence: 99%
“…Neuromotor impairment will be further assessed according to the HINE, a standardised paediatric neurological examination and classified by type. We have used both these tests extensively in previous studies in Uganda and found them easy to administer in this setting and at this age 15. The assessments will be conducted in the local language using the standard manual material to ensure internal consistency in the assessments technique.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2011, the ABAaNA studies (‘Abaana’, meaning ‘children’ in the local language Luganda) have been examining risk factors for, and outcomes from, neonatal encephalopathy (NE) in Uganda 15. Studies examining early neurodevelopmental outcomes after NE revealed a high prevalence of neurodevelopmental impairment (NDI) with 25% of those affected also having malnutrition from related feeding difficulties 15. Qualitative work highlighted the stigma and broad-ranging social, emotional and financial impacts on affected families 3…”
Section: Methodsmentioning
confidence: 99%
“…The research methodology and primary results have been described previously. [17][18][19][20] In summary, term infants (≥37 weeks gestation) with NE (Thompson score 21 ≥6 within 12 h of birth) and an unmatched comparison group of term infants without NE were included. Control infants were contemporaneously recruited (at a case:control ratio of 1:2), systematically sampled from the labor ward admission book, and were eligible if their Thompson score was <3 (as assessed by trained MNRH study physicians).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The procedure used in the current study for neurodevelopmental follow-up has been previously reported. 18 In summary, children were assessed at 12-15 and 27-30 months of age, either in outpatient clinic or at home (<5%). Transport costs were remunerated.…”
Section: Early Childhood Outcomesmentioning
confidence: 99%